LIFE OF THE CITIES OF KASHKADARYA - Abdullayeva Gulrukh (Western European Studies, 2025)
This article analyzes the social and economic life of the historical cities of the Kashkadarya region in the second half of the 18th century and the beginning of the 20th century. It covers changes in the lifestyle of the region's population, trade, crafts, land ownership and tax systems, as well as economic reforms during the period of Russian colonialism
Keywords: Kashkadarya; economy; trade